Enantioselective Organocatalytic Intramolecular Morita–Baylis–Hillman Reaction of Some Unusual Substrates - Satpathi, Bishnupada; Ramasastry, S. S. V. (Synlett, 2016)
The hypothesis and rationale behind our recent contribution towards the development of an enantioselective organocatalytic intramolecular Morita–Baylis–Hillman (IMBH) reaction, leading to the synthesis of an array of cyclopentannulated arenes and heteroarenes, is discussed. The latest advancement has addressed some of the shortcomings of the MBH reaction. In addition, it is believed that this study paves the way for the consideration of new possibilities in MBH chemistry.
Keywords: Morita–Baylis–Hillman reaction; heterocyclic compounds; organocatalysis; cyclopentannulation; natural products